Developing a measurement scale for sustainable high-rise building in city of Erbil - Baiz, Wezha Hawez; Hoskara, Ercan (Taylor & Francis Ltd, 2022)
The aim of this article is to develop a sustainable measurement scale that covers various aspects of socio-cultural, economic, and environmental activities in high-rise building constructions that are localized for Erbil city. To achieve this goal, the key methods that we used were to review the relevant literature to find the value and the global-scale rating system, which then formed the basis of the measurement and was tailored to make it more specific for high-rise projects. Discussions with relevant experts through semi-structured interviews for the localized and specialists in the measurement scale were also made. In addition to the interactions with known experts, the need for personal observation became clear. A total of five high-rise buildings were examined to understand the current scenario and preferences. Consequently, this article proposes a measurement scale for sustainable high-rise buildings (MSSHRB-E), which was specifically designed for new and existing buildings in Erbil city. This scale has nine environmental indicators, 14 socio-culture indicators, and four economic indicators, in addition to innovation issues. This research contributes to sustainable initiative methods by enhancing energy efficiency, quality of living, and cost to the users of high-rise buildings.
Keywords: Sustainability; measurement scale; indicators; high-rise buildings; Erbil city